Keragaman Jenis HHBK Kelompok Pangan pada Kawasan Hutan Buttu Puang di Desa Mirring Kabupaten Polewali Mandar - Sukri, Muhammad; Irundu, Daud (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2021)
Food is a need that must be met which then becomes the basis for determining the quality of the nation's human resources (HR) and the socio-political stability of a country. In this case, food is the most important supporting thing in a country, but it is often found that there are several food problems in an area. Forest food crops need to be introduced to overcome this problem. Mirring Village is one of the villages in Polewali Mandar Regency which has abundant food potential. This research is focused on the exploration and identification of food plant species, so that the exploration can describe areas that have the potential for sustainable food crops. This study aims to determine the Importance Value Index (INP) and the value of the Diversity Index of Food Plant Species and the utilization of food plants in the KTH Buttu Puang area. This research is a quantitative descriptive study with a census procedure. There are 30 types of food plants, with the highest IVI value of 85.27% for cocoa and the lowest value of 1.38% for dragon fruit. The diversity index value (H') is 2.02. Thus, intensive management of food plants needs to be done to maintain their sustainability.